A novel neck rejuvenation protocol using a combination of injectables and technologies in a single session - Taciana Dal'Forno; Martina Souilljee Birck (Sociedade Brasileira de Dermatologia (SBD), 2024)
Neck aging encompasses intrinsic and extrinsic factors that need to be understood in order to achieve good treatment outcomes in the area. Minimally or noninvasive methods for neck rejuvenation have gained popularity because they provide individualized, natural, and safe results with no downtime. However, few studies have debated the need for global neck treatment or have offered suggestions and ways to combine different methods in single or multiple sessions. We report here a novel protocol with the combined use of injectables and technologies in a single session, which act on laxity, fine lines, wrinkles, and skin quality.